2019
DOI: 10.3839/jabc.2019.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calendula arvensis extract on anti-melanogenesis and antimicrobial activity

Abstract: At concentrations with little or no cytotoxicity, C. arvensis extract indicates the ability of high DPPH radical scavenging, inhibited tyrosinase activity, and decreased melanin content. The treatment of B16F10 cells with C. arvensis extract suppressed the protein expression of tyrosinase a dose-dependent manner. These results suggest that C. arvensis extract inhibits melanin synthesis by inhibiting tyrosinase expression and tyrosinase activity. In addition, C. arvensis extract showed antimicrobial activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In contrast, it has been reported that C. arvensis extract is a safe natural product, as at least it did not induce any cytotoxicity at 100 μ g/mL. The cytotoxicity of this extract was 0, 0.1, 0.3, 15.1, and 28.0% at increasing concentrations of 10, 100, 250, and 500 μ g/mL, respectively [ 104 ].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, it has been reported that C. arvensis extract is a safe natural product, as at least it did not induce any cytotoxicity at 100 μ g/mL. The cytotoxicity of this extract was 0, 0.1, 0.3, 15.1, and 28.0% at increasing concentrations of 10, 100, 250, and 500 μ g/mL, respectively [ 104 ].…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, all extracts displayed good antituberculosis effects against M. smegmatis with MIC between 13.2 and 62.5 μ g [ 41 ]. According to Kim [ 104 ], C. arvensis extract had excellent antibacterial activity, and after 12 hours of culture, it inhibited the growth of B. subtilis , E. coli , and C. albicans by 40, 7, 35.2, and 27.5%, respectively. Moreover, the growth inhibitory effect against the positive bacteria, B. subtilis , was the highest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation